Influence of Wolbachia on host gene expression in an obligatory symbiosis - Kremer Natacha; Charif Delphine; Henri Hélène; Gavory Frédérick; Wincker Patrick; Mavingui Patrick; Vavre Fabrice (BMC Microbiology, 2012)
Abstract Background Wolbachia are intracellular bacteria known to be facultative reproductive parasites of numerous arthropod hosts. Apart from these reproductive manipulations, recent findings indicate that Wolbachia may also modify the host’s physiology, notably its immune function. In the parasitoid wasp, Asobara tabida, Wolbachia is necessary for oogenesis completion, and aposymbiotic females are unable to produce viable offspring. The absence of egg production is also associated with an increase in programmed cell death in the ovaries of aposymbiotic females, suggesting that a mechanism that ensures the maintenance of Wolbachia in the wasp could also be responsible for this dependence. In order to decipher the general mechanisms underlying host-Wolbachia interactions and the origin of the dependence, we developed transcriptomic approaches to compare gene expression in symbiotic and aposymbiotic individuals. Results As no genetic data were available on A. tabida, we constructed several Expressed Sequence Tags (EST) libraries, and obtained 12,551 unigenes from this species. Gene expression was compared between symbiotic and aposymbiotic ovaries through in silico analysis and in vitro subtraction (SSH). As pleiotropic functions involved in immunity and development could play a major role in the establishment of dependence, the expression of genes involved in oogenesis, programmed cell death (PCD) and immunity (broad sense) was analyzed by quantitative RT-PCR. We showed that Wolbachia might interfere with these numerous biological processes, in particular some related to oxidative stress regulation. We also showed that Wolbachia may interact with immune gene expression to ensure its persistence within the host. Conclusions This study allowed us to constitute the first major dataset of the transcriptome of A. tabida, a species that is a model system for both host/Wolbachia and host/parasitoid interactions. More specifically, our results highlighted that symbiont infection may interfere with numerous pivotal processes at the individual level, suggesting that the impact of Wolbachia should also be investigated beyond reproductive manipulations.